2018
DOI: 10.1177/1369433218810183
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of building cracks based on image processing technology with double square artificial marks

Abstract: In order to measure the crack width of dangerous buildings quickly and accurately, this article presents a new crack width measurement method, which is based on image processing technology, using double square artificial markers to identify building cracks and calculate crack width. It makes two 10 mm × 10 mm black square artificial marks and places them near the sides of the crack. Then it uses a camera to collect crack images and transfer photos to a computer. The crack image is subjected to image graying, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Using the same calculation method, /Gn1CFn by equation ( 14) was obtained at t n /Gn1CFn ¼ ACOS 1CGn 1CFn (14) In this study, the value of tilt angle change was obtained by equation (15).…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…Using the same calculation method, /Gn1CFn by equation ( 14) was obtained at t n /Gn1CFn ¼ ACOS 1CGn 1CFn (14) In this study, the value of tilt angle change was obtained by equation (15).…”
Section: Methodsmentioning
confidence: 94%
“…The angle /G01CF0 in the initial calibration image was computed by equation (13). The angle /G01CF0 in the nth image was computed by equation (14). The /GnHG0 value of building tilt angle change at nth observation was realized by equation (15).…”
Section: Building Tilt Angle Change Calculation and Real-time Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Their method is restricted to constant illumination and angle at which the image recording system is set towards the recorded surface. Yang et al [17] used an image processing technique called the double square artificial mark method to detect cracks in buildings and estimate their width. Although, it was demonstrated that their method is highly accurate in crack width estimation, it needs two black square artificial marks to be placed near the sides of the crack, which can be a restriction in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, SHM based on computer vision has attracted extensive attention in civil engineering, such as visual inspection and damage detection (Gao and Mosalam, 2018;Morgenthal and Hallermann, 2014), crack width measurement (Coca et al, 2020;Yang et al, 2019), and dynamic displacement measurement (Dong and Catbas, 2019;Dong et al, 2020). The vehicle re-identification based on computer vision in the large-scale traffic monitoring scene can be regarded as a problem of the nearest neighbor search for repetitive image retrieval (Mei et al, 2014), is of substantial significance in intelligent traffic (Zhang et al, 2011), urban computing (Zheng et al, 2014), and road travel time estimation (Kwong et al, 2009).…”
Section: Introductionmentioning
confidence: 99%